Henry and Mudge and the Funny Lunch : The Twentieth Book of Their Adventures - Rylant, Cynthia; Stevenson, Su=cie. (New York : Simon & Schuster Books for Young Readers, 1999)
Mudge looks forward to the Mother's Day surprise that Henry and his father cook up for Henry's mother.
Keywords: Dogs -- Fiction; Mother's Day -- Fiction; Fathers and sons -- Fiction; Food -- Fiction